2022
DOI: 10.3390/cancers14092086
|View full text |Cite
|
Sign up to set email alerts
|

Cancers and COVID-19 Risk: A Mendelian Randomization Study

Abstract: Observational studies have shown increased COVID-19 risk among cancer patients, but the causality has not been proven yet. Mendelian randomization analysis can use the genetic variants, independently of confounders, to obtain causal estimates which are considerably less confounded. We aimed to investigate the causal associations of cancers with COVID-19 outcomes using the MR analysis. The inverse-variance weighted (IVW) method was employed as the primary analysis. Sensitivity analyses and multivariable MR anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Based on our current findings, a worse symptom of COVID-19 does not seem to represent a risk factor for EC development, while future investigations are warranted to further establish or rule out our findings. By applying a reverse directional MR design, we further confirmed that genetically predicted female-specific cancers appear not to affect either the susceptibility or the severity of COVID-19, concordant with a previous MR study 43 .…”
Section: Discussionsupporting
confidence: 87%
“…Based on our current findings, a worse symptom of COVID-19 does not seem to represent a risk factor for EC development, while future investigations are warranted to further establish or rule out our findings. By applying a reverse directional MR design, we further confirmed that genetically predicted female-specific cancers appear not to affect either the susceptibility or the severity of COVID-19, concordant with a previous MR study 43 .…”
Section: Discussionsupporting
confidence: 87%
“…KS is the most prevalent HIV-associated malignancy and is among the top 10 cancers in most sub-Saharan Africa countries (GLOBOCAN, 2022). Despite previous studies observing no increased risk of COVID19 among patients presenting with some of the most common cancers [ 11 ], individuals with HIV-associated KS may be an exception due to the role of HIV in KS pathogenesis and in compromising T cell immunity in this population.…”
Section: Introductionmentioning
confidence: 83%
“…e controversy surrounding this issue may be due to limitations from the involvement of participants with known high-risk health behaviours, such as smoking or alcohol addiction, and family histories of cancer [9][10][11].…”
Section: Introductionmentioning
confidence: 99%